Los obstáculos y retos para la inclusión laboral de personas con discapacidad física del gad san jacinto de buena fe año 2024 - Patiño Vera, Jinyer Catherine (2025)
The research aimed to analyze the main obstacles and challenges faced by people with physical disabilities in their labor inclusion in the San Jacinto Regional Government of Buena Fe (GAD) during the year 2024. To this end, interviews were conducted with the directors responsible for the inclusion program and a survey was administered to 50 beneficiaries with physical disabilities linked to the program. The results revealed that the lack of accessibility in urban infrastructure and services in Buena Fe limits the labor inclusion of people with physical disabilities, since a high percentage of respondents perceive deficiencies in street design, access to public and private institutions, public transportation, public spaces, as well as facilities at job training sites. Significant social and cultural barriers affecting inclusion were identified, including social prejudice (30%), cultural stereotypes (28%), and a lack of appreciation for people with disabilities within the community (44%), which contributes to social resistance to full labor integration, hindering the acceptance and recognition of their potential. Finally, although GAD workers demonstrate efforts to support labor integration, perceptions differ regarding their level of commitment, the quality of technical support, the training received, and the adaptation of work activities. These findings highlight the need to implement improvements in these areas to achieve effective, sustainable, and rights-respecting labor inclusion for people with physical disabilities in the study area.